Graphene nanoplatelets size analysis based on sample transparency - Lorenc, Zofia; Tomczewski, Sławomir; Sałbut, Leszek (Photonics Letters of Poland, 2015)
<!-- saved from url=(0022)http://internet.e-mail --> The paper presents transmission characteristics of different graphene samples. Predicting affiliation to groups characterized by different size nanoplatelets and describing character of pastes was the aim of presented work. To achieve this goal authors used simple optical system in which a plane wave illumination of the sample and a telecentric imaging system were used. Analysis of intensity histograms and lowest transmission regions of nanaplatelets were done. To create a model from measured parameters, authors applied decision tree using leave-one-out cross-validation to fairly evaluate the results. Model allows to predict the size of nanoplatelets. Full Text: PDF References F. Bonaccorso et al., "Graphene photonics and optoelectronics", Nature Phot. 4(9), 611 (2010). CrossRef S. Pang et al., "Graphene as Transparent Electrode Material for Organic Electronics", Advanced Materials 23(25), 2779 (2011). CrossRef F. Wang et al., "Gate-Variable Optical Transitions in Graphene", Science 320(5873), 206 (2008). CrossRef K.S. Novoselov et al., "Electric Field Effect in Atomically Thin Carbon Films", Science 306(5696), 666 (2004). CrossRef C.R. Rao et al., "Graphene: The New Two-Dimensional Nanomaterial", Angewandte Chemie Intern. Edit. 48(42), 7752 (2009). CrossRef T. Yager et al., "Express Optical Analysis of Epitaxial Graphene on SiC: Impact of Morphology on Quantum Transport", Nano Letters 13(9), 4217 (2013). CrossRef L.C. Herrera-Ramirez et al., "How do graphite nanoplates affect the fracture toughness of polypropylene composites?", Composites Scien. Techn. 111, 9 (2015). CrossRef T. Yager et al., "Wafer-scale homogeneity of transport properties in epitaxial graphene on SiC", Carbon 87, 409 (2015). CrossRef E. Stolyarova et al., "High-resolution scanning tunneling microscopy imaging of mesoscopic graphene sheets on an insulating surface", Proc. National Academy Sciences 104(22), 9209 (2007). CrossRef J. Wang et al., "Percolation threshold and electrical conductivity of graphene-based nanocomposites with filler agglomeration and interfacial tunneling", J. Appl. Phys. 118(6), 065101 (2015). CrossRef R.G. Miller Jr., Beyond ANOVA: basics of applied statistics (CRC Press, 1997). S. Milborrow, rpart.plot: Plot rpart Models. An Enhanced Version of plot.rpart., R Package, 2011. DirectLink